"All of Me": Psychologizing Turkish‐Dutch Police Officers in the Netherlands. (December 2014) - Mutsaers, Paul
Abstract This article offers a critical take on the excessive use of psychological applications in the work sphere, that is, management techniques that open up the psyche of the individual employee to interceptions, evaluations, and manipulations by superiors. It builds upon existing work on the psychologization of labor under the aegis of human resource apparatuses and contributes to it by centralizing the role that confessions have in this process. The article details the careers of Fehim and Halil, both Turkish‐Dutch officers working for a Dutch police agency. The field data, which have been obtained through an ethnographic fieldwork between 2008 and 2013, offer an insight into how psychological applications (such as personal development plans, "fireplace sessions, " empowerment courses, personality surveys, etc.) affect labor relations. The analysis opens up pathways for a better understanding of ethnic inequality in the workplace.